2013
DOI: 10.1002/pen.23761
|View full text |Cite
|
Sign up to set email alerts
|

Conducting polymers obtained from quiescent and stirred solutions: Effects on the properties

Abstract: Poly(3,4-ethylenedioxythiophene), poly(N-methylpyr-\ud role), and three-layered systems made of alternated\ud layers of such two conducting polymers have been\ud prepared by agitating the generation solution through\ud a magnetic bar at a stirring speed of 400 rpm. The\ud influence of these controlled dynamic conditions on\ud both the electrochemical behavior and the superficial\ud morphology has been examined. Results indicate that\ud the increase in transport rate of reactants slightly\ud favors the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It should be remarked that until such study the information reported in the literature about the influence of dynamical stirring in the polymerization and properties of ECPs was very scarce [25][26][27]. This was an amazing feature since we found that controlled agitation improves significantly the flow of monomer at the electrode surface and affects the organization of polymer chains in the resulting films [24]. More specifically, our results indicated that the increase in transport rate of reactants slightly favors the generation of more polymer weight at equal charge consumed.…”
Section: Among Commercially Available Ecps Poly(34-ethylenedioxythimentioning
confidence: 84%
See 3 more Smart Citations
“…It should be remarked that until such study the information reported in the literature about the influence of dynamical stirring in the polymerization and properties of ECPs was very scarce [25][26][27]. This was an amazing feature since we found that controlled agitation improves significantly the flow of monomer at the electrode surface and affects the organization of polymer chains in the resulting films [24]. More specifically, our results indicated that the increase in transport rate of reactants slightly favors the generation of more polymer weight at equal charge consumed.…”
Section: Among Commercially Available Ecps Poly(34-ethylenedioxythimentioning
confidence: 84%
“…Figure 2a displays the electroactivity and electrostability of PEDOT films obtained using dynamic conditions and a polymerization time of 100 s. The concentration of monomer in the reaction medium was 2 mM in all cases, which was identified as the optimum value in our previous study [24], while the following LiClO4 concentrations were considered: 100, 50 and 20 mM. As it can be seen, the electroactivity increases with the concentration of supporting electrolyte, even though the charged stored in 7 PEDOT films prepared using 100 and 50 mM LiClO 4 is relatively similar (i.e.…”
Section: Influence Of the Supporting Electrolyte Concentration Using mentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, we used the layer‐by‐layer (LbL) electrodeposition technique to prepare nanostructured conducting systems based on three alternated layers of poly(3,4‐ethylenedioxythiophene) (PEDOT) and poly( N ‐methylpyrrole) (PNMPy) , hereafter abbreviated 3l‐PEDOT/PNMPy (i.e., PEDOT/PNMPy/PEDOT). These multilayered materials showed better electrochemical properties and a higher ability to store charge than each of the two individual CPs and the corresponding copolymer, poly(3,4‐ethylenedioxythiophene‐ co ‐ N ‐methylpyrrole), hereafter named COP .…”
Section: Introductionmentioning
confidence: 99%